2009
DOI: 10.1007/s00066-009-1904-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Radiotherapy for Brain Metastases on Quality of Life (QoL)

Abstract: Practicability and compliance appeared better with the (shorter) version B. This version is now used in the ongoing main phase of the study with additional centers. First results indicate a moderate worsening of QoL during the first 3 months after start of palliative radiotherapy for brain metastases. QoL at initiation of radiotherapy may be prognostic for survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
1
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 24 publications
4
58
1
3
Order By: Relevance
“…This finding was also observed in the study by Steinmann et al, which employed the QLQ-BN20 in conjunction with either the QLQ-C15-PAL or the QLQ-C30 to assess QOL in patients with brain metastases [21]. The present study additionally draws attention to the potential psychological implication of this finding as future uncertainty was found to negatively correlate with overall QOL before and 1 month after treatment.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This finding was also observed in the study by Steinmann et al, which employed the QLQ-BN20 in conjunction with either the QLQ-C15-PAL or the QLQ-C30 to assess QOL in patients with brain metastases [21]. The present study additionally draws attention to the potential psychological implication of this finding as future uncertainty was found to negatively correlate with overall QOL before and 1 month after treatment.…”
Section: Discussionsupporting
confidence: 85%
“…While the QLQ-BN20 and QLQ-C30 used in this study provide a comprehensive overview of QOL, the task of completing 50 questionnaire items can be quite arduous for patients with poor performance status and mental status. In the multicentre pilot study by Steinmann et al, examining the effects of radiotherapy for brain metastases on quality of life, patients were either asked to complete the QLQ-C30 or QLQ-C15-PAL in addition to the QLQ-BN20 [21]. The EORTC QLQ-C15-PAL is a 15-item version of the 30-item QLQ-C30, designed especially for palliative cancer patients with the intent of decreasing assessment burden among the advanced cancer patient population.…”
Section: Discussionmentioning
confidence: 99%
“…As we have demonstrated, content validation of the EORTC QLQ-BN20+2 when used concurrently with the EORTC QLQ-C15-PAL for patients with brain metastases, these two QOL tools should be used in future clinical trials involving these patients. 14 Have you had difficulty in concentrating on things, like reading a newspaper or watching television?…”
Section: Resultsmentioning
confidence: 99%
“…The use of the EORTC QLQ-BN20+2 with the QLQ-C15-PAL to assess QOL was first reported in 108 patients undergoing various treatments for brain metastases [19]. The questionnaires showed maintenance (no deterioration) of QOL and improvement in a few QOL scores, which was echoed by a study that used the QLQ-BN20 with the QLQ-C15-PAL to reduce patient burden [14]. It was suggested that these two questionnaires replace the use of the QLQ-BN20 and QLQ-C30 combination previously used in many brain metastases studies in order to decrease attrition rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation